Teacher’s Strategies In Teaching English Vocabulary at SMPN 1 Tanjungpinang - Dinda Widianda; Fauzan Abdul Hakim; Rizky Aditya; Fitri Noviyanti; Erwin Pohan (EDUJ : English Education Journal, 2024)
The purpose of this study is to outline the methods that educators employ when instructingstudents in language. Qualitative descriptive research examines information gathered fromEnglish teachers' interviews. Considering the outcomes, inferences regarding the teacher'stactics have been drawn from the interviews. The instructors that are employed include: (1)Game Use: Teachers play games like "scramble for word meaning," look for synonyms andantonyms, and translate terms in English. (2) Using a Student Ability Level-BasedApproach Three groups of students are formed: Low-level: To encourage interest inEnglish, learning is made more enjoyable and participatory. High and medium level: amore somber strategy with difficult assignments and minimal gameplay. (3) MakingVocabulary Development a High Priority Teachers are aware that students' inadequatevocabulary is the biggest barrier to learning English. In order for pupils to be prepared fora higher level of learning and comprehend the material more readily, the emphasis isplaced on vocabulary development. (4) Technology Utilization: Worksheets and Quizizz areexamples of digital media that are used to add variety and interest to learning. (5) LanguageApproach: Teachers aid pupils in understanding concepts by selecting simpler terms,offering synonyms, or supplying equations in Indonesian. (6) Rewards as Motivation:Students are encouraged to compete and learn more enthusiastically by receiving thereward.